EFFECTS OF ANTHROPOMORPHISM THROUGH ILLUSTRATION, NEED FOR COGNITION, AND ARGUMENT QUALITY ON ATTITUDES TOWARD USING REUSABLE WATER BOTTLE OF COLLEGE STUDENTS - Kaewwanich, Rattanakorn; Boonyasiriwat, Watcharaporn (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The present research aims to study effects of anthropomorphism, need for cognition, and argument quality on attitudes toward using reusable water bottle of college students on campus. In this experiment, 222 undergraduate students reported their need for cognition, then were randomly assigned to read either strong or weak argument in a persuasive message, with either anthropomorphism or non-anthropomorphism illustration before completing a measure of attitudes toward using reusable water bottle on campus, and a thought-listing task. A conditional process analysis via PROCESS [1] showed that there is a significant three-way interaction between anthropomorphism, need for cognition, and argument quality on attitudes toward using reusable water bottle (b = -.05, p<.05). Simple slope tests show significant effects of need for cognition on attitudes toward using reusable water bottle when the message contains weak argument and anthropomorphism illustration (b = .03, p<.01), and also when the message contains strong argument quality and non-anthropomorphism illustration (b = .04, p<.05). These findings are important for understanding the effects of anthropomorphism on pro-environmental attitudes.